A Case of Fracture-Redislocation of the Hip Caused by a Depressed Fracture of the Femoral Head Similar to a Hill-Sachs Lesion. (18th May 2017) - Okudera, Yoshihiko; Kijima, Hiroaki; Yamada, Shin; Konishi, Natsuo; Kubota, Hitoshi; Tazawa, Hiroshi; Tani, Takayuki; Suzuki, Norio; Kamo, Keiji; Sasaki, Ken; Kawano, Tetsuya; Iwamoto, Yosuke; et al.
Abstract : The present case shows a case of fracture-redislocation of the hip caused by a depressed fracture of the femoral head similar to a Hill-Sachs lesion. A 59-year-old man fell from a roof and his left hip joint was dislocated posteriorly. He was admitted to a nearby hospital, and he was referred to our hospital more than 24 hours after injury. Computed tomography (CT) suggested a bone chip from the posterior wall of the acetabulum roof and a depressed femoral head that cut into the posterior margin of the acetabulum roof. Immediate manual repositioning was performed under general anesthesia on the same day. He left our hospital to go home on day 26 after repositioning, but his left hip joint was dislocated again when he went down the stairs. It was thought that this patient's redislocation occurred due to a femoral head depressed fracture involving the same mechanism as the Hill-Sachs injury seen with dislocation of the shoulder. The remplissage method for the Hill-Sachs injury is difficult for the femoral head. Therefore, total hip replacement was performed, and the patient's postoperative course was good. We conclude that total hip arthroplasty should be considered as one of the best treatment methods for such cases.